MOTIVASI DAN KEPUTUSAN WISATAWAN NUSANTARA BERWISATA BELANJA KE TEMAN JOGER BALI - Juniawan, Made (Jurnal IPTA (Industri Perjalanan Wisata), 2023)
Shopping tourism has become an attractive choice for tourists to visiting Bali. However, shopping tourism leads to modern souvenirs store, and leaves the traditional art market which was previously a favorite place for shopping tourism. Thereiareimany factorsithat influenceitheidecision of tourists to choose a modern souvenir store such as Teman Joger. Motivation has become a push factor from within to satisfy all needs and desires, as well as a factor underlying the determination of tourist decisions. Data presented in this research were collected through distributing questionnaires to domestic tourists who visiting Teman Joger, interviews with related parties, and other sources. This research concludes that there are seven factors that influence motivation to Teman Joger, namely personality, internal, prestige, social, gratification, product, and physical. This research also found that motivation has a positive relationship and significantly influences to tourist decisions in Shopping Tourism at Teman Joger, with a percentage of 35.7 percent. This means that the decision of tourists in choosing the modern souvenir store that is Teman Joger, is influenced by 35.7 percent by motivational factors, while the other is influenced by other factors not explained in this study.